PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN, PROFITABILITAS, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN (PERIODE 2013-2015) - Fifin Setiani, 14.05.52.0052; Lisiantara, G. Anggana (Students Journal of Accounting and Banking, 2018)
The firm value shows that the prosperity of stakeholder will increased as well. The firm value becomes very important because it reflect the performance of the company which can influence the perception of investors to the company. This research is meant to find out the influence of firm size, the growth of the company, profitability, capital structure, and liquidity to the firm value. The samples are 211 manufacturing companies which are listed in Indonesia Stock Exchange (IDX) during the 2013-2015 periods and they have been selected by using purposive sampling. The statistic test instrument uses SPSS 20 version wich is carried out to perform classic assumption test, multiple linear regressions analysis, and the hypothesis test. The result of the hypothesis test shows that : (1) firm size does have any influence to the firm value ; (2) the growth of the company does not have any influence to the firm value; (3) profitability of the company does not have any influence to the firm value;(4) capital structure does not have any influence to the firm value ; (5) liquidity does not have any influence to the firm valueKeywords : Firm Size, The Growth Of The Company, Profitability, Capital Structure, Liquidity and firm value.